2004
DOI: 10.1021/jp036307c
|View full text |Cite
|
Sign up to set email alerts
|

ESR and HRTEM Study of Carbon-Coated Nanocrystalline MgO

Abstract: Carbon-coated nanocrystalline MgO samples were prepared by butadiene pyrolysis at 500 °C over aerogelprepared MgO samples. Samples with carbon loadings of 1.2, 3.2, 5.0, 10.0, and 15.9 wt % were prepared. Initial carbon formation rate was about 2 wt % per hour. According to HRTEM, the structure of the mineral component in the carbon-mineral materials was not altered by the carbon deposition. At low loading of carbon, it was found to deposit only inside the MgO aggregates 5-10 nm from their outside surface, for… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
25
1
3

Year Published

2008
2008
2021
2021

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 37 publications
(29 citation statements)
references
References 16 publications
0
25
1
3
Order By: Relevance
“…19,23 Earlier we have reported that the carbon coating deposited on the surface of the oxide nanoparticles can act as a nanoreactor shell. On the one hand, such coating can be penetrable for the reactant molecules from the gas 7,10,24,25 or liquid 26 phases making it possible to initiate various catalytic or solid-state reactions inside the nanoreactor. Moreover, the carbon coating prevents sintering of nanoparticles inside the shell during the temperature increase and stabilizes their sizes.…”
Section: Introductionmentioning
confidence: 99%
“…19,23 Earlier we have reported that the carbon coating deposited on the surface of the oxide nanoparticles can act as a nanoreactor shell. On the one hand, such coating can be penetrable for the reactant molecules from the gas 7,10,24,25 or liquid 26 phases making it possible to initiate various catalytic or solid-state reactions inside the nanoreactor. Moreover, the carbon coating prevents sintering of nanoparticles inside the shell during the temperature increase and stabilizes their sizes.…”
Section: Introductionmentioning
confidence: 99%
“…MgO, CaO, and Al 2 O 3 [12][13][14][15]; MgO [16][17][18][19]; MgO, CaO, and Fe 2 O 3 [20]; Al 2 O 3 /MgO physical mixture [21], other oxides coated [22,23] or doped on CaO and MgO [24] were studied as destructive adsorbents for DMMP, other organophosphorus, fluoro-, chloro-, bromocarbons, and sulfur compounds. Nanocrystalline MgO, CaO, and Al 2 O 3 have shown remarkably high capacities to chemically adsorb organophosphorus compounds [12].…”
Section: Introductionmentioning
confidence: 99%
“…For organophosphorus compounds the heats of adsorption were found high and shown a small dependence on the substituent effects [16]. In the most cases, destructive adsorption, taking place on the surface of the MgO nanocrystals, proceeds so that the adsorbate is chemically dismantled and thereby made nont-oxic [18,19]. Decomposition of organophosphorus compounds on MgO surface proceeds due to yielded formic acid [20].…”
Section: Introductionmentioning
confidence: 99%
“…These are conventional basic sites and low-coordinated surface ions, as well as highly active oxygen radical anions, electron-donor sites and acid sites identified using adsorption of nitroxyl radicals. 16,17,19,20 Oxygen radicals were observed on the MgO surface only after illumination in a vacuum installation and were not detected during reactions with halocarbons. Therefore, our main attention was attracted to highly active electron-donor and electron-acceptor sites.…”
Section: Characterization Of Electron-donor and Electron-acceptor Sitmentioning
confidence: 99%